Assessment of the lactate and ventilatory thresholds by breathing frequency in runners - Jones, A. M.; Doust, J. H. (Journal of Sports Sciences, 1998)
The aim of this study was to establish the validity of the breakpoint in breathing frequency for the assessment of the lactate threshold and the ventilatory threshold during incremental running exercise. We conclude that the breakpoint in breathing frequency does not provide a valid method for the field-based assessment of the lactate or ventilatory thresholds in most subjects for running exercise.